All Days 2010
DOI: 10.2118/134613-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Applications in Heavy Oil EOR with the Nanoparticle and Surfactant Stabilized Solvent-Based Emulsion

Abstract: This study presents the results of nano-particle and surfactant-stabilized solvent-based emulsion bench test studies under laboratory conditions that investigate the recovery mechanisms of chemical flooding in a heavy oil reservoir. In the study, bench tests, including the phase behavior test, rheology studies and interfacial tension measurement are performed and reported for the optimum selecting method for the nano-emulsion which is going to be applied in the coreflooding experiments. Specifically, nanoemuls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 3 publications
1
31
0
Order By: Relevance
“…Qiu et al [130] evaluated the potential application of NP-stabilized solvent base emusion injection to enhance heavy oil recovery in the Alaska North Slope area. The experimental results showed that addition of NPs to micro-emulsions increased the viscosity of the micro-emulsion, resulting in a favorable mobility ratio.…”
Section: Nano-assisted Emulsion Floodingmentioning
confidence: 99%
“…Qiu et al [130] evaluated the potential application of NP-stabilized solvent base emusion injection to enhance heavy oil recovery in the Alaska North Slope area. The experimental results showed that addition of NPs to micro-emulsions increased the viscosity of the micro-emulsion, resulting in a favorable mobility ratio.…”
Section: Nano-assisted Emulsion Floodingmentioning
confidence: 99%
“…The presence of suspended nanoparticles in the solution increases sedimentation stability, because surface forces easily counterbalance the force of gravity. In addition, it is obvious that surfactants contribute to the stability of nanoparticles and emulsions to decrease IFT [65,87].…”
Section: Effects Of Nanoparticles On Ift Reductionmentioning
confidence: 99%
“…The study of the emulsion stability and phase behavior are reported and the emulsion's piston-like front flooding is observed. Qiu and Mamora [25,26] In view of the surfactant-stabilized emulsions cannot withstand harsh reservoir conditions and has low viscosity, this study takes advantage of the synergistic effect of silica nanoparticle and surfactant, which can not only improve the emulsions stability, but can also significantly increase the bulk viscosity of emulsion to the desirable mobility. Thus, the nanoparticle-surfactant stabilized emulsion will be less prone to viscous fingering and should lead to improved sweep efficiency.…”
Section: Introductionmentioning
confidence: 99%